Antioxidant characteristics and quality assessment of soymilk supplemented with Ocimum basilicum L. - Jin, Suyeon; Ju, Hyun-Mok; Kim, Sujin; Lee, Jihee; Kwon, Ki Han (Progress in Nutrition, 2017)
Soymilk is used as a milk substitute for people with lactose intolerance. Recent research has aimed to fortify the health/functional aspect of soymilk. Hence, in order to investigate the potential of soymilk as a drink with improved functionality, Ocimum basilicum L. (Basil) was added to soymilk and the quality and antioxidant effects were comparatively analyzed. The addition of basil did not affect the water content or chromaticity of soymilk, and the pH of soymilk decreased as the concentration of basil increased. Although total phenol content significantly increased as the concentration of basil increased, total flavonoid content did not show a significant change. Moreover, the antioxidant effect significantly increased as the concentration of basil increased, suggesting that this effect is attributed to the phenol contained in basil. Results of the sensory evaluation suggest that overall evaluation was unfavorable since the aroma of basil grew stronger as the concentration of basil increased. Thus, while soymilk supplemented with basil has excellent antioxidant capacity, future studies on the growth conditions and processing of basil are needed to reduce its unique aroma and thus enable production of fortified soymilk with good flavor.